(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: identifying the rate of vitamin D deficiency and analyzing certain factors related to vitamin D deficiency in children aged under 6 in Nghe An obstetrics and pediatrics hospital in 2023. Subject and research method: 2367 children diagnosed with plasma vitamin D concentration by Nghe An obstetrics and pediatrics hospital. This is a Cross-sectional descriptive research. Result: Among 2367 children researched, the rate of vitamin D deficiency is 32.91%. The average concentration of vitamin D of the subjects is 38.49 ng/ml. The rate of vitamin D deficiency in girls is 34.4%, higher than boys’ 31.7%. The highest vitamin D deficiency rates belong to Children aged under 6 months and 24-72 months with 47.6% and 40.6% respectively. Conclusion: the rate of vitamin D deficiency in children aged under 6 diagnosed in Nghe An obstetrics and pediatrics hospital in 2023 is 32.91%. There is a relationship between anemia, iron deficiency, calcium deficiency and Vitamin D deficiency.